(822) Bibliographical Guide to The UN Mimeographed Documents دليل بيبلوجرافى لوثائق الامم المتحدة المنسوخة ( المدونة بخط اليد ) - Mahmoud M. Afifi; Sohair Zakaria; Farouk Farag; Mahmoud Eid (INP, 2024)
The Documentation Center has prepared this "Bibliographical Guide to the U.N. Mimeographed Documents" to aid researchers in accessing materials related to consultations within U.N. Councils and Committees. Covering the period from 1965 to 1967, the guide will be updated periodically based on new material. It follows the U.N.'s classification system, arranging entries alphabetically and numerically by series symbol and document number, and includes an index of issuing bodies' titles. The guide aims to support studies across various fields of economic and social development.